Internalized homonegativity/homophobia is associated with HIV-risk behaviours among Ugandan gay and bisexual men. (May 2013) - Ross, M W; Kajubi, P; Mandel, J S; McFarland, W; Raymond, H F
Summary: We investigated the relationship of internalized homonegativity/homophobia (IH) to sexual risk behaviours among 216 Ugandan gay and bisexual men, using the 7-item IH scale previously developed on this population. IH was significantly associated with unprotected anal intercourse, and more so with unprotected receptive anal intercourse. Higher IH was also associated with more sex while intoxicated. There was a strong association between anal intercourse of any type and IH, suggesting a complex relationship between anal sex and identification with, or internalization of, homonegativity/homophobia. Specifically, it may be the anal component of sex rather than the sex with another man that is seen as labeling one as homosexual or stigmatizing. Those men who stated that they engaged in sex with other men for love, rather than for the physical feeling or for money, had higher IH scores. These data suggest that there may be an interactive relationship between IH and sexual behaviour, with greater internalization being associated with more stereotypically gay activities, which in turn may lead to more self-identification as gay and thus greater susceptibility to internalization.